Client Satisfaction with Urban Family Physician and Referral System in the South of Iran: A Repeated Cross-Sectional Study - Alireza Mirahmadizadeh; Maryam Marzban; Maryam Siadati; Karam Tavani; Abdolrasul Hemmatid (Shiraz University of Medical Sciences, 2017)
Background:Patient satisfaction is an integral component of service quality and obtaining feedback from patients about the quality of primary health care is the best way to extend more patient-centered goals to health care delivery. This study was conducted to measure the level of client satisfaction with Urban Family Physician and Referral System (UFPARS) programMethods: This repeated cross-sectional study was done in Fars province, South of Iran, at two sections. Totally, 5901 patients in two sections (6 and 24 months after the UFPARS startup) were selected using multi-stage random sampling. The participants answered a self-administrated questionnaire. We measured the client satisfaction using 5-point Likert-scaled score and combined the questions; for each component of UFPARS, 6 satisfaction dimensions were made. We compared the participants' level of satisfaction in two parts, using t-test.Results: Reliability was acceptable, and equal to 85% or more in all domains .In all components of UFPARS, the mean client satisfaction score was higher than 3 out of 5. The lowest client satisfaction scores were seen in the outpatient services. In three components of UFPARS including enrolment, family medicine and para-clinics, the mean satisfaction scores significantly decreased (P<0.001) between the two sections. But other components showed no significant change. Conclusions:The level of satisfaction with UFPARS in Fars province was shown to be relatively medium to high. Low client satisfaction between the two sections could be a bad sign and we recommend that the problems should be tackled gradually. Although family physician program in Iran has some limitations, implementing this plan step by step can lead to a medical reform in Iran. We can develop better programs based on the comments from service recipients, and prompt the project and some program processes.